THE ROLE OF SPIRITUAL VALUES IN RAISING THE MORALE OF THE PEOPLE - Matluba Minavarovna Yuldasheva (Scholar Express Journals, 2021)
The article focuses on the nature of harmful ideas that run counter to our national interests and way of life, as well as issues related to the negative impact of extremist currents on the minds of our citizens. In general, the conveniences created by globalization are emerging as an effective tool for self-serving forces. They use such tools extensively in the field of economic potential, technical and technological progress, as well as in the field of spirituality, and artificially raise their philosophy, norms and criteria of social development to the level of "world standard".
Keywords: Man; society; history; ideology